Computationally efficient methods for solving optimal power flow problems by exploiting supplementary information - Barzegar, Ali Reza (2019)
Motivated by the important role of electrical energy in the quality of life in cities, the electric power flow management, scheduling, and optimization is a critical task, especially in large-scale power systems. The power flow equations as the heart of power system operation translate the power injections and voltages steady-state relationship. The nonlinearity of the power flow equations makes the optimal power flow (OPF) problem a nonconvex NP-hard optimization problem which usually has multiple optima. The complexity of the OPF problem increases significantly as the size of the power system increases, so obtaining an optimal solution for an OPF problem within a reasonable time is one of the main challenges in the optimization of the power system research area.